In Silico Study and In-Vitro Activity of Buds Cloves (Syzygium aromaticum L.) of Nonvolatile Compounds as Anticancer by Inhibiting Cell Cycle Regulators - Rosmalena, Rosmalena (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: In order to investigate the potential biological activities, we simulated a series of cyclin-dependent kinases (CDKs) (CDK1, CDK2, and CDK6 series) with molecular docking approach experiments to identify the bioactive compounds and evaluated the in vitro antitumor activity of ethanol extract of buds cloves (EEBC). In addition, we conducted a series of experiments to identify the potential biological mechanisms of the EEBC. Material and Methods: In this study, we investigated in silico molecular docking to know about their molecular mechanisms of EEBC and the active components for cytotoxic activity. This research was carried out using AutoDock4 software. To prove the in silico docking result, we also investigated the cytotoxic effects of EEBC using cell lines of human cancer. Results: Based on all the docking result, Myricetin and Quercetin in EEBC played a main role as CDKs inhibitor because they showed very good free energy binding against CDK2, CDK6, and CDK1. IC50 values of EEBC (IC50 of 24.45 Î¼g/ml) on HCT-116. Conclusion: EEBC could be potential sources from natural products that have cytotoxic properties against colorectal cancer through CDKs inhibition mechanism.